ANALISIS PERHITUNGAN AUDIT ENERGI PADA SISTEM KELISTRIKAN GEDUNG ASRAMA UNIVERSITAS TEKNOLOGI SUMBAWA - Bagus Saputra AB; Desi Maulidyawati; Nova Aryanto; Ahmad Jaya (Jurnal Altron, 2023)
The development of science and technology in the world has created many new innovations, including electronic equipment. The use of electronic devices in everyday life is very easy and effective. Along with technological developments and the magnitude of developments in the above sectors in the province of West Nusa Tenggara, the demand for electrical energy always increases every year. To overcome the wasteful use of energy which will result in an increase in electricity payments, energy efficiency must be carried out. The UTS Dormitory Building, as a middle-level consumer of electrical energy, needs to be analyzed to determine the level of energy consumption efficiency. The purpose of this study was to determine the Energy Consumption Intensity (IKE) in the kWh meter of the Sumbawa University of Technology dormitory and to determine the level of energy consumption and efficiency in the kWh meter of the Sumbawa University of Technology dormitory. The method used in this study was a mixed method (Mixed Method). Research, namely by combining the types of qualitative and quantitative methods. The results of the study obtained that the energy consumption intensity value each year in the kWh of the dormitory building is 12.89 kWh/m2/year. This value is included in the efficient category according to the ASEAN-USAID IKE value standard, namely for a hotel/apartment building the maximum is 300 kWh/m2/year. The value of energy consumption intensity (IKE) every year in kWh of dormitory buildings is included in the efficient criteria.